The Exploration of Mathematical Creative Thinking Ability in Solving Geometry Problems from the Perspective of Mathematical Ability - Safaria, Sri Anandari; Agus, Imaludin (Universitas Islam Ahmad Dahlan (UIAD), 2024)
Creative thinking abilities are developed through divergent thinking in mathematics learning. This research aims to explore junior high school students' mathematical creative thinking abilities in solving geometric problems, specifically in terms of their overall mathematical abilities. This study is a qualitative descriptive research project. The subjects were 27 eighth-grade students from a state middle school in Loghia District. Data were collected using tests and interviews. The findings indicate that junior high school students with high mathematical abilities demonstrated creative thinking in solving geometric problems. In contrast, students with moderate and low mathematical abilities showed less creative thinking, particularly when answering questions about surface area and volume. Specifically, there were 3 students identified as creative, 4 students as less creative, and 20 students as not creative. Overall, most junior high school students were not creative in their approach to solving geometric problems. They struggled to demonstrate indicators of creative mathematical thinking, such as fluency, flexibility, and novelty.